2014
DOI: 10.1097/der.0000000000000044
|View full text |Cite
|
Sign up to set email alerts
|

Latex Glove–Related Symptoms Among Health Care Workers

Abstract: The hospital housekeepers emerged as the job with the significantly higher prevalence rate of glove-related symptoms than that of the other job categories. Factors associated with glove-related cutaneous symptoms are frequency and duration of glove use, history of atopy, and history of allergy to fruit cross-reacting with latex. The quantity of glove use, history of atopy, and allergy to fruits cross-reacting with latex are risk factors for the occurrence of glove-related noncutaneous symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 11 publications
2
13
0
1
Order By: Relevance
“…Thus, the positive response for skin prick test is shown in 20%, for patch test in 15% and for challenge test in 7.5% of cases. The prevalence's variation between diverse allergic pathologies has been noted in a recent survey, which reported for glove-related cutaneous and non-cutaneous symptoms in 11.3% and 5.9% of the respondents [4]. This finding also suggests that respiratory exposure plays an important role, in addition to dermal exposure [5,21].…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Thus, the positive response for skin prick test is shown in 20%, for patch test in 15% and for challenge test in 7.5% of cases. The prevalence's variation between diverse allergic pathologies has been noted in a recent survey, which reported for glove-related cutaneous and non-cutaneous symptoms in 11.3% and 5.9% of the respondents [4]. This finding also suggests that respiratory exposure plays an important role, in addition to dermal exposure [5,21].…”
Section: Discussionsupporting
confidence: 53%
“…This can suggest that questionnaire statements in concert with diagnostic tests are more convincing and conclusive when the pathologic processes and disease's installation reach an advanced stage due to latex exposure along years of dental practice [24]. This is reinforced by the finding that quantity of gloves use should be considered a risk factor for latex allergy, and the recent confirmation that some commercial tests are useful diagnostic tools only for patients with a history of latex allergy and not for screening the population with a low prevalence of latex sensitization [4,24].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Additionally, our study revealed concentration changes during the work practice. A skin allergy is confirmed on about 15% and non-cutaneous allergy in about 4% of subjects, indicating that, apart from contact to the skin, the respiratory exposure plays an important role on the latex sensitization [5,14,15].…”
Section: Discussionmentioning
confidence: 97%
“…The moderate correlation between some study items and exposure duration puts forth the argument that latex concentration, frequency and duration of glove use are important factors associated to latex sensitization, and to occurrence of different allergic symptoms [8,9,14,16,17]. It is estimated that duration of glove use more than 18…”
Section: Discussionmentioning
confidence: 99%